Odpowiedzi

2010-02-04T18:38:21+01:00
A) 4x-3=3x+5
4x-3x=5+3
x=8
b) 5x+2=7-3x
5x+3x=7-2
8x=5
x=5/8

c) 3(x-1)=0
3x-3=0
3x=3
x=1

d) -6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30
x=-5

e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15
x=1,5

f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=-5
2010-02-04T18:38:52+01:00
A) 4x-3=3x+5
x=8
b) 5x+2=7-3x
8x=5
x= 5/8
c) 3(x-1)=0
3x-3=0
x=1
d) -6(x+1)=24
-6x-6=24
x=-5
e)-7(x-2)=3x-1
-7x+14=3x-1
-10x=-15
x=1,5
f) 4(x-1)=6(1+x)
4x-4=6+6x
-2x=10
x=-5
2010-02-04T18:44:30+01:00
A) 4x-3=3x+5
4x-3x=5+3
x=8

b) 5x+2=7-3x
5x+3x=7-2
8x= -5//: 8
x=-5/8

c) 3(x-1)=0
3x-3=0
3x=0+3
3x=3//:3
x=1

d) -6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30//:(-6)
x= -5

e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15//:(-10)
x= 1.5
f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x= 10//:(-2)
x=-5